"I Wish Dance Class NEVER Ended": An Activist Approach to Teaching Dance. Issue 2 (3rd April 2022) - Shilcutt, Jackie Beth; Oliver, Kimberly L.; Aranda, Raquel
ABSTRACT: In an attempt to respond to the calls for dance educators to explore alternatives to harmful authoritarian teaching practices, we propose that one such route forward is an Activist Approach to teaching, which was originally developed in physical education contexts as a student-centered, inquiry-based approach that attends to issues of embodiment while listening and responding to students over time. The purpose of this study is to describe what an Activist Approach to teaching looks like in dance. Specifically, we discuss how we used an Activist Approach in an after-school dance club to co-create a curriculum with youth dancers. Data collection occurred for one year of dance club at middle school charter school in a southwest border community. We describe and reflect on our process of co-creating the learning environment and co-constructing the curriculum with the dancers to facilitate their interests, motivation, and learning.